Should all CAR-T therapy for acute lymphoblastic leukemia Be consolidated with allogeneic stem cell transplant?. Issue 4 (December 2022) - Marinos, Alejandro; Heslop, Helen E.
Abstract: Autologous T cells genetically modified with a CD19 chimeric antigen receptor are an effective therapy for children and adults with relapsed or refractory acute lymphoblastic leukemia with initial response rates ranging from 70 to 85%. Unfortunately, about half of these responding patients will subsequently relapse raising the question of whether allogeneic hemopoietic stem cell transplant should be considered as a consolidative therapy. Currently efforts are focused on defining risk factors for relapse to try and develop algorithms predicting which patients may benefit from allogenic transplant.